1987
DOI: 10.1111/j.1432-1033.1987.tb10815.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the structural requirements for proliferation of peroxisomes and mitochondria in mouse liver by hypolipidemic agents, with special emphasis on structural analogues of 2‐ethylhexanoic acid

Abstract: We have found here that there are clear structural requirements for peroxisome proliferation (monitored as increases in carnitine acetyltransferase activity, cyanide‐insensitive palmitoyl‐CoA oxidation, catalase and increases in the protein designated PPA 80) in mouse liver. From the investigation of ten structural analogues of 2‐ethylhexanoic acid, it could be concluded that the most effective proliferators all have an ethyl group as the substituent on carbon 2 of the main chain, which consists of six carbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…It is worth noting that CLA added to the assay medium inhibited the ethanolamine‐specific PLBE reaction in a concentration‐dependent manner by 40% at a concentration range of 0.5–1 mM, probably due to the reduction of essential –SH groups in the enzyme. Another possibility is that the effect of starvation and CLA administration on increased synthesis of PE could be correlated to the elevated expression of cytochrome P450 isoenzymes [9–12]. In fact, in the course of our studies we have observed that enhancement of PE content in ER membranes from starved and CLA‐treated animals in comparison to rats fed ad libitum correlates well with the elevated expression of the cytochrome P450 CYP4A1 isoform, as detected using specific antibodies against rat CYP4A1 (Fig.…”
Section: Resultssupporting
confidence: 51%
“…It is worth noting that CLA added to the assay medium inhibited the ethanolamine‐specific PLBE reaction in a concentration‐dependent manner by 40% at a concentration range of 0.5–1 mM, probably due to the reduction of essential –SH groups in the enzyme. Another possibility is that the effect of starvation and CLA administration on increased synthesis of PE could be correlated to the elevated expression of cytochrome P450 isoenzymes [9–12]. In fact, in the course of our studies we have observed that enhancement of PE content in ER membranes from starved and CLA‐treated animals in comparison to rats fed ad libitum correlates well with the elevated expression of the cytochrome P450 CYP4A1 isoform, as detected using specific antibodies against rat CYP4A1 (Fig.…”
Section: Resultssupporting
confidence: 51%
“…The ligand which binds to PPAR upon treatment of rodents with peroxisome proliferators is not yet known. One suggestion is that xenobiotic acyl-CoA derivatives bind to PPAR, since the vast majority of peroxisome proliferators contain a carboxylic moiety or another group which can be metabolized to such a moiety in uivo [6,7]. An alternative hypothesis is that peroxisome proliferators disturb cellular lipid metabolism such that an endogenous ligand for PPAR accumulates.…”
Section: ( I ) What Is the Mechanism Underlying Peroxisome Proliferatmentioning
confidence: 99%
“…The structural requirements for chemicals that cause hepatic peroxisome proliferation have been examined (100)(101)(102). The only unifying theme with regard to the diverse chemical structures which cause peroxisome prolifera tion is that they all contain an acid function or are readily metabolized to a 1.…”
Section: Receptor-mediated Mechanismmentioning
confidence: 99%